So it Happened… What Now? : The Evolution of a Reflections-based Course for Students Involved in Academic Misconduct - Jordaan, Francois; Gervais, Loie; Dumontet, Monique (Canadian Perspectives on Academic Integrity, 2023)
Academic integrity and academic misconduct are issues that affect all post-secondary institutions, and the University of Manitoba has seen a rising number of cases (Annual Report of the University Discipline Committee, 2021). Furthermore, there has been a call (Bertram Gallant, 2008; Sopcak & Hood, 2022) for developing and implementing responsive educational approaches in academic misconduct cases at the post-secondary level. These educational approaches move away from quasi-legal and punitive measures, which have been shown to negatively impact the well-being of the involved students (Pitts et al., 2020). Instead, it has been argued that academic misconduct should be addressed as a learning, teaching and skills development concern. In this presentation, we discuss the implementation of a reflection-based course for students involved in cases of academic misconduct. Completion of this self-directed online course is the preliminary step in educational outcomes for most students involved in academic misconduct at the University of Manitoba. We chart the shift in this educational outcome from a quiz-based tutorial to a multi-module -reflection-based approach. We will discuss the rational and practical implications of the “Reflections on Academic Integrity (RAI)” course. We will argue that the RAI course actively and consciously moves away from the stigmatization associated with academic misconduct towards framing the student’s experiences as a learning outcome that sets the foundation for a return to successful studies.